1989
DOI: 10.1007/bf00326592
|View full text |Cite
|
Sign up to set email alerts
|

The fate map of the chick forelimb-bud and its bearing on hypothesized developmental control mechanisms

Abstract: Carbon particles and isotopic quail grafts were used as markers to study the salient features of the fate map of the chick forelimb between stages 20 and 27. The grafting technique confirmed the reliability of the carbon method: they both revealed striking asymmetries in which apical mesodermal tissue was progressively displaced in a proximal direction (as would be expected on the basis of growth by net apical addition of tissue) but also in a preaxial direction, while postaxial tissue became elongated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 31 publications
5
35
0
Order By: Relevance
“…The ectodermal sheet remains anchored distally and expands by proximal stretching (Bowen et al, 1989). This relationship between the ectoderm and apical mesoderm may be significant considering other aspects of limb development.…”
Section: Discussionmentioning
confidence: 98%
“…The ectodermal sheet remains anchored distally and expands by proximal stretching (Bowen et al, 1989). This relationship between the ectoderm and apical mesoderm may be significant considering other aspects of limb development.…”
Section: Discussionmentioning
confidence: 98%
“…In both, this pattern is only partly tempered distally by the growth-promoting properties of the apical ectodermal ridge (AER), perhaps because of the more-posterior placement of the AER (Todt and Fallon, 1984). Anteroposterior differences in growth rate seem to increase with age, such that the faster growing posterior region forms more of the limb's distal structures (Bowen et al, 1989). In the present study, there were no clear anteroposterior differences in growth in DM, although they are suggested by the data for older stage 23-24 limbs (Fig.…”
Section: A-mentioning
confidence: 99%
“…Differences along this axis have been demonstrated in organ culture (Suzuki and Ide, 19871, but reflect mainly ectodermal restriction of chondrogenesis to the limb core since anteroposterior differences in ectoderm-free explants were not observed. The similar in vitro chondrogenic capacity of anterior and posterior limb mesenchyme has been puzzling because fate maps (Bowen et al, 1989) and tissue ablation studies (Hinchliffe and Gumpel-Pinot, 1981) suggest that most of the limb's distal cartilages derive from postaxial mesenchyme. In the present study, anteroposterior differences in in vitro chondrogenesis were detected in SCM (Fig.…”
Section: Region-dependent Chondrogenic Capacity Of Wing-bud Mesenchymementioning
confidence: 99%
“…This observation suggests that the volumetric growth pattern in chick wing development is multiphasic; after the uniform growth in earlier stages, the growth pattern shifts to distally biased one. The spatially heterogeneity of volumetric growth rate after stage 23 is also supported by the study by Bowen et al (1989) who examined the relationship of 2D position of each cell (2D fate map) among different stages 21, 24, and 27. On the other hand, Lewis (1975) examined a 1D fate map and concluded that the length growth along the P-D axis is spatially uniform until stage 25.…”
Section: (Iii) Parameter Rangesmentioning
confidence: 74%
“…Fate map data indicate the movement of a marked cell during some time interval, and provide information potentially important in estimating the spatiotemporal pattern of volumetric growth rate (Stark and Searls, 1973;Lewis, 1975;Bowen et al, 1989;Vargasson et al, 1997;Clarke and Tickle, 1999;Sato et al, 2007;Pearse et al, 2007). In principle, we could readily do it if we knew the positions of every cell at every time, that is, if we had fate map data with infinite resolution on space and time.…”
Section: Introductionmentioning
confidence: 99%